FORMULATION AND IN-VITRO EVALUATION OF GLIPIZIDE LOADED MICROSPHERES PREPARED WITH PECTIN EXTRACTED FROM DILLENIA INDICA & ABELMOSCHUS ESCULENTUS. - SIVASANKAR MOHANTY; GOTTUMUKKALA KRISHNA MOHAN (International Journal of Pharma and Bio Sciences, 2015)
The purpose of this research was to formulate and evaluate mucoadhesive microspheres of glipizide by using pectin obtained from Dillenia indica & Abelmoschus esculentu.The Glipizide microspheres were prepared by w/o emulsion solvent evaporation method by using different variables like concentration of surfactant, polymer-to-drug ratio, and rotation speed of mechanical stirrer. The polymers like pectin obtained from Dillenia indica & Abelmoschus esculentus by acetone precipitation method. The prepared microspheres were characterized for the percentage yield, drug entrapment efficiency, FTIR, DSC, SEM analysis and in-vitro drug release studies. Microspheres were obtained are discrete, spherical, and free flowing. The microspheres exhibited good mucoadhesive property in the in vitro wash-off test and also showed high percentage drug entrapment efficiency (58.7 ± 1.2- 88.1 ± 0.9 %). The FTIR & DSC studies showed the stable character of glipizide in the microspheres. The SEM analysis revealed that the microspheres were spherical, non aggregating and they were nonporous in nature. The study concluded that that the pectin obtained from Dillenia indica & Abelmoschus esculentus can be used as a promising polymer for glipizide microspheres & giving opportunity to use in various novel drug delivery systems.